'They help us realise what we're actually gaining': The impact on undergraduates and teaching staff of displaying transferable skills badges. (March 2022) - Hill, Michelle A; Overton, Tina; Kitson, Russell RA; Thompson, Christopher D; Brookes, Rowan H; Coppo, Paolo; Bayley, Lynne
Attaining transferable skills is increasingly important for undergraduates and, while such skill development may be embedded within the curriculum, it is often not well recognised by students. This mixed methods study explores the use of skills badges as icons displayed on curriculum materials in several disciplines at two universities. The badges are designed to draw students' attention to skill development opportunities; an approach that is easily scalable in any discipline. Results indicated that more than half of students found the badges helpful and their recognition of the development of some skills increased. Other benefits included understanding the wider purpose of learning tasks, increased motivation and satisfaction and identification of examples for use in the job application process. The badges prompted some staff to communicate with students about skills and to re-evaluate their teaching approach to maximise skill development opportunities. Communication between staff and students is key to ensuring students understand the purpose of the badges and how to use them.